Tailored Solution‐Based N‐heterotriangulene Thin Films: Unravelling the Self‐Assembly. Issue 11 (5th May 2021) - Hawly, Tim; Streller, Fabian; Johnson, Manuel; Miguez‐Lago, Sandra; Hammer, Natalie; Hampel, Frank; Vivod, Dustin; Zahn, Dirk; Kivala, Milan; Branscheid, Robert; Spiecker, Erdmann; Fink, Rainer H.
Abstract: The ability of a series of bridged triarylamines, so‐called N ‐heterotriangulenes, to form multilayer‐type 2D‐extended films via a solution‐based processing method was examined using complementary microscopic techniques. We found that the long‐range order, crystallinity, and layer thickness decisively depend on the nature of the substituents attached to the polycyclic backbone. Owing to their flat core unit, compounds exhibiting a carbonyl unit at the bridge position provide a superior building block as compared to thioketone‐bridged derivatives. In addition, nature and length of the peripheral substituents affect the orientation of the aromatic core unit within highly crystalline films. Hence, our results stress the significance of a suitable molecular framework and provide deeper understanding of structure formation in 2D‐confined surroundings for such compounds. Abstract : Towards layered organic electronics : The in‐plane and out‐of‐plane alignment as well as the morphology of solution‐processed N ‐heterotriangulene films is found to depend on the nature of the bridge and peripheral substituents attached to the core unit. Spectromicroscopic characterization allows for the understanding of structure formation under 2D‐confined conditions and illustrates the significance of a customizable molecular framework for well‐defined layered systems.